Efficiency, responsiveness and stability of maize hybrids under low nitrogen availability conditions - Carvalho, Maisa Nascimento [UNESP]; de Oliveira, Gustavo Hugo Ferreira; de Souza Júnior, Claudio Lopes; Môro, Gustavo Vitti [UNESP] (My University, 2023)
Growing maize has required ever greater use of nitrogen fertilizers, increasing costs and possible environmental contamination. In this respect, the aim of this study was to characterize single cross maize hybrids under conditions of low and high nitrogen availability to identify them in regard to efficiency, responsiveness, and stability in relation to N. A total of 49 single-cross maize hybrids were evaluated in seven environments in square lattice design. Two experiments were conducted: one with application of nitrogen in top dressing and the other without application. Grain yield without application of nitrogen and grain yield with application of nitrogen were evaluated and, from these estimates, the agronomic efficiency at low N availability and the harmonic mean of the relative performance (HMRP) were obtained. Analysis of variance, the Scott-Knott test, and characterization of the efficiency and responsiveness of the hybrids were carried out. Hybrids with greater stability were identified by HMRP, and 23% of the hybrids were classified as efficient and responsive. Of the hybrids evaluated, 67% can be used to increase nitrogen use efficiency in breeding programs.
Eficiência, responsividade e estabilidade de híbridos de milho sob condições de baixa disponibilidade de nitrogênio
Keywords: agronomic efficiency of nitrogen use; genotype by environment interaction; harmonic mean of the relative performance; Zea mays L